Analysis of Feasibility and Effectiveness Organizational Behaviour 3D Realist Teaching Material Based on Project Learning - Saragih, Lenti Susanna; Dharma, Jufri; Siahaan, Sabda Dian Nurani (PT FORMOSA CENDEKIA GLOBAL, 2023)
Realist 3D videos are teaching materials that can make it easier for students to understand the context of learning material to make it easier to apply it in a project. This study aims to determine the level of feasibility, practicality and analyze the impact of using teaching materials on student learning outcomes. The study was carried out for 1 year. The method used in this study is the R&D Method using the ADDIE model. The study population is 6th semester Business Education Study Program students. Data collection techniques use observation and questionnaires. Data is processed using descriptive analysis. Based on the results of the study, it can be concluded that teaching materials for Organizational Behavior with 3D Realist videos Based on Project Based Learning are feasible and practical to use. Based on the effectiveness test, it is known that there are differences in learning outcomes before and after treatment using teaching materials.